Efek Daya Hambat Kombinasi Fraksi Polar F33-F37 Elephantopus scabr dengan Amoksisilin dan Kloramfenikol terhadap Staphylococcus aureus dan Escherichia coli - Firsania Bunga W (Jurnal Kedokteran Komunitas, 2019)
Introduction: A combination of herb and antibiotic is an alternative treatment for infectious disease. The herb that has been studied before is E.scabr which was found that crude extract was antagonistic with chloramphenicol. Possibly, that interaction can happen because of the active compounds effect that is contained in the extract. Fractination is necessary to separate the active compound from E.scabr  which may affect the combination interaction. The result of fractionation will be tested for phytochemicals identification from the fraction 33-37 E.scabr and measured for antibanterial activity with amoxicillin and chloramphenicol  against S.aureus and E.coli.Methods: The ZOI test was carried out by the Kirby-Bauer method, then the clear zone was measured using a ruler. Antibiotic interactions is interpreted by the AZDAST guideline.Results: Single ZOI test in fraction 33 E.scabr obtained clear zone with 9.33 ± 1.53 mm diameter against S. aureus, whereas in other fractions no clear zone was found. Combination of E.scabr fraction with amoxicillin and chloramphenicol in ZOI test for S. aureus cannot be distinguished from the single test. Combination of fraction 35 with chloramphenicol against E. coli showed a significantly decreased result from a single test with a value of F35 0 ± 0 mm, chloramphenicol 18 ± 1 mm and a combination of F35 with chloramphenicol 16 ± 1 mm.Conclusion: Fraction 35 E.scabr obtained antagonistic interactions with chloramphenicol against E. coli, whereas in other fractions the interaction could not be determined (not distinguishable) in amoxicillin and chloramphenicol against S. aureus and E. coli. An alkaloid compound is an ingredient in F35 which is thought to affect the interaction.Keywords: Amoxicillin, Chloramphenicol, E.scabr, Combination of Herbal Antibiotics